Environmental Disaster Education at University: An Overview in New Normal of COVID-19 - Alim, Alimun Nasrun A. Hi; Rahmayanti, Henita; Husen, Achmad; Ichsan, Ilmi Zajuli; Marhento, Giry; Alamsyah, Mashudi; Susilo, Susilo; Babu, R. Udhaya Mohan; Rahman, Md. Mehadi (International Journal for Educational and Vocational Studies, 2020)
Pandemic Coronavirus Disease (COVID-19) is a non-natural disaster that occurs globally. Disaster mitigation efforts need to be made when entering a new normal life after the physical distancing policy is relaxed. The purpose of this study was to describe the knowledge and participation of students in disaster mitigation activities during the new normal period. The research method used descriptive, data collection techniques through Google Form with a sample of 54 students. The results showed that learning of disaster mitigation education is not maximally taught at the university level with a percentage of 57.4% for students, who did not receive disaster mitigation education. However, as many as 51.9% of students had attended training in disaster education. Disaster mitigation education was important to do when a new normal period. That is because students are one component that has a role to convey various information about the disaster, especially COVID-19. This study concludes that knowledge and student participation in disaster education still needs to be improved. The suggestion from this research was necessary to develop innovative learning tools for disaster mitigation education in the new normal era of COVID-19.